Re-aktualisasi Kujang Ciung Sebagai Personifikasi Karakter Game Senjata Tradisional Pulau Jawa - Tiara Radinska Deanda (DeKaVe, 2018)
Abstract.Indonesia has a rich culture and has a lot of ancestral artifacts that are not widely known by its own people and one of them is a traditional weapon. For example, the island with the most populous population in Indonesia, namely Java. Traditional weapons on the island of Java began to be forgotten and not well known by the community, especially by the younger generation. One of the traditional weapon is Kujang Ciung. Today's young generation still thinks that traditional weapons that are commonly heard can only be used for rituals without knowing what history and the meaning behind it. This was due to the lack of appeals and information regarding traditional Indonesian weapons.This phenomenon is the basis of the designer to create a design that can impact the young generation so that they are motivated and provoked to preserve their own traditional weapons, such as a game design. Game as a medium that continues to evolve as well as one of the technologies that is close to the younger generation. One of the ways to introduce weapons (kujang), is to make a personification based of Kujang weapons that will become one of the characters in the game. Personification method will be used so that the younger generation can get to know kujang in a more simple and interactive way. Smartphone will be used as its platform because the younger generation is more accustomed to gadgets and technology. This design research will use a qualitative descriptive approach with Case Study, Content and Image Analysis methods to examine references that can be used as a strong foundation in making personification of Kujang as a character in the traditional Java island weapons game.Keywords:personification, Kujang Ciung, digital game